Composite Sn-Fe oxide as a compatible OER electrocatalyst for electrochemical alkaline water electrolysis - Velluva, Abhijai; Christi, Darren Sebastian; Selvaraj, Kaliaperumal (Journal of Physical Chemistry C, 2026)
Green hydrogen production through electrochemical water splitting is one of the optimal replacements for conventional fossil fuel energy sources. The development of highly active and electrochemically stable non-noble-metal electrocatalysts for the sluggish oxygen evolution reaction (OER) is considered to be an important step in decreasing the energy requirement during alkaline water electrolysis. Herein, we report a Sn-doped FeOx composite (SnFeOx) powder, which could be synthesized through a single-step hydrothermal method and is reported for the first time for OER during electrochemical water electrolysis. SnFeOx exhibits a low eta(100) (overpotential at 100 mA cm(-2) current density) value of 288 mV and a good Tafel slope of 35 mV dec(-1) in 1 M KOH, which surpasses the performance of standard non-PGM OER catalysts. A long-durability test at a higher current density of 100 mA cm(-2) for 50 h reveals the excellent activity retention of SnFeOx (>99%). The suitability of SnFeOx for full-water splitting was tested with Pt/C as a cathode electrode, and Pt/C/NF||SnFeOx/NF exhibited a lower eta(10) value of 1.56 V that is superior to Pt/C/NF||Ru/C/NF (1.59 V) with more than 99% retention at a current density of 10 mA cm(-2) for 50 h. The more favorable OER performance of SnFeOx compared to FeOx can be attributed to the successful Sn4+ doping along with increased oxygen defective sites and larger electrochemical surface area.